Structural and analytical studies on some complexes of Pd2+ ions with asymmetric -dioximes - Daniela Cîrțînă (Journal of Research and Innovation for Sustainable Society)
Starting from the favorable analytical properties of -asymmetric dioximes in the chemical analysis of certain transition metal ions, new methods for quantitative determination of Pd2+ with aliphatic and alkyl-aryl dioximes were developed. A comparative study was conducted on the selectivity and sensitivity of the color and precipitation reactions of the analyzed - asymmetric dioximes, investigating how the nature of the R and R' radicals linked to the dioxime group influences the physico-chemical properties, on the one hand, of the ligands and the complexes formed, and, on the other hand, influences their solubilities and gravimetric factors. The experimental data carried out have highlighted the increased sensitivity and selectivity of the color reactions of asymmetric α-dioximes with Pd2+ ions. This is why new gravimetric and spectrophotometric methods have been developed for the determination of these cations in the form of asymmetric dioximates.